1836 Tenn. Comp. Stat. 325, Felonies, 1829—Chapter 23, § 56 - (:unkn) unknown (General Publisher, 1836)
If any person within this state shall fight a duel, or shall deliberately and maliciously challenge, by word or writing, any other person, to fight with sword, pistol, or other deadly weapon, or shall deliberately and maliciously invite another verbally, or by writing, to meet him in this state, or elsewhere, with a view or intent to challenge or fight; or if any person so challenged, shall deliberately and maliciously accept the said challenge, in either case, such person so deliberately and maliciously giving or receiving, or sending any such challenge, and being convicted thereof, shall be sentenced to imprisonment, at hard labor in the penitentiary, for a term not less than three nor more than ten years: Provided always, that no person who shall be verbally challenged, shall be a competent witness to prove the fact of such verbal challenge, against any person who may be indicted for the same.
--
Keywords: DUELING